Efficacy of emerging therapies versus traditional therapies in the treatment of hypertrophic scars and keloids: a systematic review - Alzate, Juan; Villamil-Guevara, Johanna; Adarme-Malaver, Juliana; Gutiérrez-Ochoa , Laura; Acevedo Piedrahita , Laura; Pinilla-Obregon , Mariana (Aesthetic Medicine, 2025)
Introduction: Hypertrophic scars and keloids are abnormal wound-healing alterations that disproportionately affect populations of African, Asian, and Latin descent. Traditional therapies, such as surgery, corticosteroids, and laser treatments, demonstrate limited effectiveness and frequent recurrence. Emerging therapies, including mesenchymal stem cells and growth factors, hold promise for improved inflammatory regulation and tissue remodeling. Objective: To compare the efficacy and safety of emerging therapies versus traditional treatments in reducing hypertrophic scars and keloids, evaluating aesthetic outcomes, scar size, and recurrence rates. Methods: A systematic review was conducted in accordance with PRISMA guidelines, including 8 studies with 525 participants. The interventions assessed comprised mesenchymal stem cells, platelet-rich plasma, and triamcinolone-laser combinations. Primary outcomes were volume reduction, aesthetic improvement, and decreased recurrence. Results: Emerging therapies, such as platelet-rich plasma, showed significant reductions in the Vancouver Scar Scale (p<0.05) and decreased profibrotic markers such as CTGF (40%-50% reduction). Traditional treatments, like intralesional triamcinolone, achieved an average scar volume reduction of 90.1% within one year (p=0.031) but were associated with greater adverse effects, such as hypopigmentation. Combined therapies offered improved aesthetic results with a lower incidence of side effects. Discussion: Emerging therapies demonstrate significant potential, particularly in reducing profibrotic factors and achieving an initial aesthetic improvement. However, they present limitations regarding standardization and long-term sustainability. Traditional therapies, while effective, require combinations to minimize recurrence and adverse effects.